Diagnostic accuracy of early computed tomographic coronary angiography to detect coronary artery disease after out-of-hospital circulatory arrest. (August 2020) - Branch, Kelley R.; Hira, Ravi; Brusen, Robin; Maynard, Charles; Kudenchuk, Peter J.; Petek, Bradley J.; Strote, Jared; Sayre, Michael R.; Gatewood, Medley; Carlbom, David; Counts, Catherine; Probstfield, Jeffrey L.; et al.
Abstract: Aim: To test the diagnostic accuracy of ECG-gated coronary computed tomography angiography (CCTA) to detect coronary artery disease (CAD) among survivors of out-of-hospital circulatory arrest (OHCA). Methods: We prospectively studied head-to-pelvis computed tomography (CT) scanning (<6 h from hospital arrival) in OHCA survivors. This sub-study tested the primary outcome of CCTA diagnostic accuracy to identify obstructive CAD (≥50% stenosis) compared to clinically-ordered invasive coronary angiography. Patients were not optimized with beta receptor blockade or nitroglycerin. Secondary analyses included CCTA accuracy for CAD in major coronary arteries, obstructive disease at ≥70% stenosis threshold, and where non-evaluable CCTA segments were considered either obstructive or non-obstructive. Results: Of the 104 enrolled OHCA survivors, 28 (27%) received both CT and invasive angiography in this sub study. All CCTA studies were evaluable although 49/346 (14%) individual coronary segments were unevaluable, primarily due to being too small to evaluate (65%). Patient-level diagnostic accuracy for the ≥50% stenosis threshold was high at 0.93 (95% CI 0.77–0.98) with a specificity of 1.0 (95% CI 0.8–1.0), sensitivity of 0.85 (95%CI 0.58–0.96), negative predictive value of 0.88 (95% CI 0.66–0.97) and positive predictive value of 1.0 (0.74–1.0). When non-evaluable segments were considered obstructive, the sensitivity rose to 0.92 (95% CI 0.67–0.99) with lower specificity of 0.27 (95% CI 0.11–0.52). Conclusion: Early CCTA of OHCA survivors has high diagnostic accuracy to detect obstructive coronary artery disease. However, the number of non-diagnostic coronary segments is high suggesting further CCTA refinement is needed, such as the pre-CCTA use of nitroglycerin. Clinical Trial Registration: NCT03111043 https://clinicaltrials.gov/ct2/show/record/NCT03111043